2014
DOI: 10.1097/id.0000000000000122
|View full text |Cite
|
Sign up to set email alerts
|

Implant Associated Soft Tissue Defects in the Anterior Maxilla

Abstract: Within the limitations of this study, both SCTG and ADM result in increased mucosal thickness, reduction in concavity dimensions, and have a potential for recession reduction on definitively restored dental implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(108 citation statements)
references
References 54 publications
1
107
0
Order By: Relevance
“…The full-text assessment was performed for 66 studies. Based on predetermined inclusion criteria, 19 articles were included in the qualitative analysis (Anderson et al, 2014;Baldi et al, 2020;Bianchi & Sanfilippo, 2004;Cairo et al, 2017;De Bruyckere et al, 2020;Fenner et al, 2016;Froum et al, 2015;Huber et al, 2018;Hutton et al, 2018;Lorenzo et al, 2012;Roccuzzo et al, 2016Roccuzzo et al, , 2019Schallhorn et al, 2015;Thoma et al, 2016Thoma et al, , 2020Vellis et al, 2019;Wiesner et al, 2010;Zucchelli et al, ,2013Zucchelli et al, , , 2018. The reason for exclusion of the 47 records is reported in the Appendix (Table 1).…”
Section: Search Results and Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The full-text assessment was performed for 66 studies. Based on predetermined inclusion criteria, 19 articles were included in the qualitative analysis (Anderson et al, 2014;Baldi et al, 2020;Bianchi & Sanfilippo, 2004;Cairo et al, 2017;De Bruyckere et al, 2020;Fenner et al, 2016;Froum et al, 2015;Huber et al, 2018;Hutton et al, 2018;Lorenzo et al, 2012;Roccuzzo et al, 2016Roccuzzo et al, , 2019Schallhorn et al, 2015;Thoma et al, 2016Thoma et al, , 2020Vellis et al, 2019;Wiesner et al, 2010;Zucchelli et al, ,2013Zucchelli et al, , , 2018. The reason for exclusion of the 47 records is reported in the Appendix (Table 1).…”
Section: Search Results and Study Selectionmentioning
confidence: 99%
“…Other studies have compared PROMs of autogenous grafts vs. substitutes, and reached either similar or conflicting results (Anderson et al, 2014;Huber et al, 2018;Lorenzo et al, 2012;Thoma et al, 2016;Vellis et al, 2019). However, a comprehensive review focusing on PROMs following peri-implant soft tissue grafting procedures has not yet been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Use of an acellular dermal matrix was associated with impaired wound healing and more exposure compared to autogenous soft tissue grafts, but its volume stability in the long term must be established. 39 Several types of autogenous soft tissue grafts are used to treat peri-implant recession in properly placed implants. Studies report outcomes from CTG removed from the palate using the single incision technique and free gingival grafts that were de-epithelized or removed from the tuberosity.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are few prospective studies that address this type of defect, partial to full coverage may be expected depending on the extent of the clinical alteration and overall prognosis. 2,12,38,39 Shibli et al 40 proposed one of the first published methods to treat PIR in 2004 and reported that recession was successfully treated by using a combination of prosthetic and surgical procedures. The abutment diameter and provisional were initially reduced in its facial aspect followed by a coronally advanced flap (CAF) that was associated with a thick CTG graft (Figure 2).…”
Section: Peri-implant Recessionmentioning
confidence: 99%
See 1 more Smart Citation